Pengembangan Aplikasi Sistem Informasi Manajemen Surat Berbasis Web Di Desa Jumput Sukosewu: Rizky Stighfarrinata - Stighfarrinata, Rizky (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Mail management is a crucial component of formal communication and organizational administration, whether in small, medium, or large entities. Incoming and outgoing mail within an organization, including government bodies, holds strategic value as a communication tool, memory archive, authentic record, and guide for carrying out activities. In Jumput Village, Sukosewu, Bojonegoro, mail management is still conducted manually, which presents various challenges, such as the risk of lost archives and slow administrative processes. To address this, a Community Service initiative was undertaken to simplify mail management by developing a web-based Mail Management Information System. This application is designed to store incoming mail, outgoing mail, letter dispositions, and other important documents, such as Village Regulations (PERDES), Village Head Decrees (PERKADES), and Village Consultative Body Decrees (BPD). The application supports various file formats, including jpg, jpeg, png, pdf, doc, docx, xls, and xlsx, with a maximum file size of 20MB, tailored to the needs identified through interviews with the Village Secretary and Village Head. The implementation of this system is expected to enhance efficiency in the administrative management of Jumput Sukosewu Village, facilitate easier archiving, and reduce the workload of administrative staff. Therefore, this application is anticipated to provide an effective solution for digitizing mail management at the village level.